# algebra

posted by .

Radicals are so confusing. Can someone show me step by step please. Im lost

5/8+√7

• algebra -

The main point is to recall that (a-b)(a+b) = a^2-b^2

So, if you want to get rid of roots in the denominator, multiply top and bottom by the "conjugate" expression

(8+√7)(8-√7) = 8^2 - √7^2 = 64-7 = 57

So,

5/(8+√7) = 5(8-√7)/((8+√7)(8-√7))
= 5(8-√7)/57
= (40 - 5√7)/57

## Similar Questions

1. ### Algebra

How do I solve for the elimination method: 5x + 3y= -7 and 7x - 2y =13 (step 1); 10x + 6y =-14 and 21x -6y = 39 ( step 2), 31x/31= 25/31, x= 25/31 (step 4). But after that I get lost. Can somebody help me out please.
2. ### Algebra II

I need to rewrite this with rational exponents. (√3mn)^9 I have no clue of what I need to do. Can someone please take me step by step?
3. ### Physics

Can someone please show me step by step how to normalize e^-5x in the interval (0, infinity)?

Please show work Simplify rational 1. 4√(a^6 b^13) / 4√(a^2b) 2.√(2x^3 / 49y^4) Add or Subtract 3. x√(75xy) - √(27x^3y) Multiply 4.(√(5) - 5) (2√(5) + 2) Rationalize the denominator 5. √(25x^5 …
5. ### algebra

Can someone help me find value of x. please show step by step examples 6/x = 7/x+3
6. ### algebra

Can someone show me step by step examples of simplifying 3√5/64 thank you
7. ### algebra

please help im lost the instructions are to solve by using thee quadriatic formula and prove your answers are correct but i don't know how can someone show mw step by step how to do this so i can do my homework x^2-3x+4=0
8. ### Algebra 1--Step-by-Step

Can someone show me how to solve these step-by-step?
9. ### Chemistry

In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step
10. ### Math

I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − …

More Similar Questions

Post a New Question